THE EFFECT OF MUROTTAL QUR’AN ON MENSTRUAL PAIN IN NURSING STUDENT OF UNIVERSITAS NAHDLATUL ULAMA SURABAYA - Yurike Septianingrum; Nety Mawarda Hatmanti; Andikawati Fitriasari (Nurse and Health: Jurnal Keperawatan, 2019)
Background: Primary dysmenorrhea is menstrual pain that is found without significant abnormalities in genital organs. More than 50% of women experience primary dysmenorrhea and 15% experience severe pain. Most women never have their primary dysmenorrhea examined by a doctor or midwife, arguing that this is something natural, even if this condition is left unchecked, symptoms of endometriosis will emerge that can affect women's fertility.Objectives: The purpose of this study was to examine the effect of Murottal Qur’an on menstrual pain in nursing students of UNUSA.Method: This study was an experimental research approach with pre-test post-test design at UNUSA. Research subjects of this study was recruited using simple random sampling who was included inclusion criteria. Research subjects in this study was of 32 students who were then divided into two groups, 16 students into intervention group and 16 students into control group. Data were collected by using observation with VAS. Data were analyzed by using sign test and Mann-Whitney U test.Results: The results showed that: 1) Score of VAS in intervention group post testwas less than pre test (p= 0,000), 2) Score of VAS in intervention group was less than control group (p= 0,006). Conclusion: Murottal Qur’an could reduce menstrual pain in nursing student of UNUSA. Further research, is expected that Murottal Qur'an can be compared with music therapy to reduce menstrual pain. Keywords: Menstrual pain, Murottal Qur’an, primary dysmenorrhea.